The reproducibility of blood acid base responses in male collegiate athletes following individualised doses of sodium bicarbonate: A randomised controlled crossover study - Gough, L. A.; Deb, S. K.; Sparks, A. S.; McNaughton, L. R. (Sports Medicine, 2017)
Background: Current evidence suggests sodium bicarbonate (NaHCO3) should be ingested based upon the individualised alkalotic peak of either blood pH or bicarbonate (HCO3-) because of large inter-individual variations (10-180 min). If such a strategy is to be practical, the blood analyte response needs to be reproducible. Objective: This study aimed to evaluate the degree of reproducibility of both time to peak (TTP) and absolute change in blood pH, HCO3- and sodium (Na+) following acute NaHCO3 ingestion. Methods: Male participants (n = 15) with backgrounds in rugby, football or sprinting completed six randomised treatments entailing ingestion of two doses of 0.2 g·kg-1 body mass (BM) NaHCO3 (SBC2a and b), two doses of 0.3 g·kg-1 BM NaHCO3 (SBC3a and b) or two control treatments (CON1a and b) on separate days. Blood analysis included pH, HCO3- and Na+ prior to and at regular time points following NaHCO3 ingestion over a 3-h period. Results: HCO3- displayed greater reproducibility than pH in intraclass correlation coefficient (ICC) analysis for both TTP (HCO3- SBC2 r = 0.77, P = 0.003; SBC3 r = 0.94, P < 0.001; pH SBC2 r = 0.62, P = 0.044; SBC3 r = 0.71, P = 0.016) and absolute change (HCO3- SBC2 r = 0.89, P < 0.001; SBC3 r = 0.76, P = 0.008; pH SBC2 r = 0.84, P = 0.001; SBC3 r = 0.62, P = 0.041). Conclusion: Our results indicate that both TTP and absolute change in HCO3- is more reliable than pH. As such, these data provide support for an individualised NaHCO3 ingestion strategy to consistently elicit peak alkalosis before exercise. Future work should utilise an individualised NaHCO3 ingestion strategy based on HCO3- responses and evaluate effects on exercise performance.